2012
DOI: 10.1007/s00705-012-1443-3
|View full text |Cite
|
Sign up to set email alerts
|

SEN virus detection in thalassemic patients infected with hepatitis C virus

Abstract: HCV infection is known to be associated with clinical complications in thalassemic patients. D and H genotypes of SEN virus (SENV) are associated with blood-product transfusion and possibly non-A-to-E hepatitis. In this study, SENV viremia and its effect on liver ALT level in thalassemic patients, thalassemic patients infected with HCV, and HCV-infected patients were examined. Semi-nested PCR was conducted for detection of genotype H and D DNA, and the level of alanine aminotransferase (ALT) was measured. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Further, the significantly greater occurrence of SENV infections among patients with thalassemia than among healthy donors remains suggestive of blood transfusions being the primary source of SENV infections in patients with thalassemia [13]. Sani et al [14] reported SENV viremia in 90.0% of patients with thalassemia (regardless of their HCV infection status) and in 76.7% of patients with HCV infections. These results are similar to the SENV infection rates reported in Taiwan [15].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the significantly greater occurrence of SENV infections among patients with thalassemia than among healthy donors remains suggestive of blood transfusions being the primary source of SENV infections in patients with thalassemia [13]. Sani et al [14] reported SENV viremia in 90.0% of patients with thalassemia (regardless of their HCV infection status) and in 76.7% of patients with HCV infections. These results are similar to the SENV infection rates reported in Taiwan [15].…”
Section: Discussionmentioning
confidence: 99%
“…Furthe, the significantly greater occurrence of SENV infections among patients with thalassemia than among healthy donors remains suggestive of blood transfusions being the primary source of SENV infections in patients with thalassemia [13]. Sani et al [14] reported SENV viremia in 90.0% of patients with thalassemia (regardless of their HCV infection status) and in 76.7% of patients with HCV infections. These results are similar to the SENV infection rates reported in Taiwan [15].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%